Metal oxides carbon xerogel nanocomposite for methanol oxidation fuel cell - Fatma Mohamed; Mohamed Shaban; Omnia M. Salem (Scientific Reports)
Abstract The primary requirement for electrode materials in direct methanol fuel cells (DMFC) is efficient electrocatalyst that exhibit high tolerance to methanol oxidation, excellent stability, and reasonable cost. The combination of distinct active materials with distinctive architectures may facilitate the attainment of this objective. The present study included the preparation of a Carbon Xerogel Doped with various metal oxides derived from Banana peels. The nanocomposites were thoroughly examined utilizing several characterization modalities including XRD, FTIR, and SEM. The electrocatalytic performance of Carbon xerogel doped with Iron (Fe3O4/CX), carbon xerogel doped with magnesium (MgO/CX), and carbon xerogel doped with Copper (CuO/CX) about the Methanol Oxidation Reaction (MOR) was investigated using electrochemical methods such as cyclic voltammetry, impedance spectroscopy, and chronoamperometry. The results showed that the Fe3O4/CX, MgO/CX, and CuO/CX are effective electrocatalysts with an onset potential of around 1.00 V and current densities of approximately 42.98 mA cm − 2, 28.2784 mA.cm − 2, and 6.60698 mA.cm − 2, respectively, in the optimized electrolyte for methanol oxidation. The stability of Fe3O4/CX, MgO/CX, and CuO/CX electrodes was examined using chronoamperometry and the Cyclic Stability method. The results revealed that the (Fe3O4/CX) electrode exhibited outstanding stability throughout the whole 60-minute chronoamperometry Technique and demonstrated great stability for 100 cycles in the Cyclic Stability technique. The remarkable electrochemical activity and stability may be attributed to the synergistic effect of Fe3O4/CX, which provided sufficient active sites for methanol electro-oxidation and reduced the equivalent series resistance, as shown by the electrochemical impedance spectroscopy analysis. This work used environmentally friendly materials, which presents a novel opportunity to enhance the efficiency of methanol oxidation via the utilization of affordable catalysts. This study of the theoretical technique methods for establishing the route of methanol decomposition, and systematizes their confirmation with experimental data, within the methodological framework.